Infections in surgery: Round table: HIV infection in surgery - Savio, Eduardo; Morelli Brum, Raúl; Carrerou, Luis A.; Cimarra, Luis F. (Cirugía del Uruguay, 1997)
Epidemiology, diagnostic criteria and clinical therapeutic considerations. The risks of the health team and HIV. Role of the surgeon in the HIV / AIDS patient.